The Influence of Najwa Shihab's “3 Bacapres Bicara Gagasan” on the Preferences of First-time Voters Regarding the 2024 Presidential Election - Teresa Alena Lee; Gema Nusantara Bakry (Journal of Government and Politics (JGOP), 2024)
“3 Bacapres Bicara Gagasan” is a livestream talk show by Najwa Shihab which lets the 3 “Bakal Calon Presiden” (presidential candidate) share their ideas and dreams for the future Indonesia and was first broadcast through Narasi TV’s website, Najwa Shihab’s YouTube channel, and Universitas Gadjah Mada’s YouTube channel. Since then, the snippets have been spread widely throughout every social media, such as Facebook, Instagram, X, and TikTok. Using quantitative methods, this research aims to see whether there are influences of the “3 Bacapres Bicara Gagasan” broadcast and snippets, which are available and have become a major conversation on social media, on first-time voters preferences regarding the 2024 presidential election. The sample size is 100 respondend using slovin’s formula of sampling. This research shows that the snippets or informations spread to social media does effect the preferences of first-time voters, such as their opinion and likes towars which candidate. However, it shows negative results towards voters’ candidate criterias. Voters’ understanding toward the show also don’t show any influence toward first-time voter’s preferences regarding the 2024 presidential elections.